Pansclerotic Morphoea - Kishore B Nanda; Lawande Lairai; Shetty J N (Wolters Kluwer Medknow Publications, 2000)
An eight year old girl presented with progressive stiffness of the right lower limb resulting in joint immobility and apparent shortening causing limitation of movement.